A cinema of one’s own - Damiens, Caroline (HAL CCSD, 2014)
International audience This paper discusses indigenous cinema from Siberia and how this media is being used by the Siberian minorities as a means to (re)build their national identity after the collapse of USSR. It focuses on films from Sakha (Yakutia) Republic and the Republic of Khakassia, both autonomous republics within the Russian Federation, which are experiencing an ethnicity-based cultural revival. It shows that cinema plays a full part in this revitalization process. The article begins with a brief history of Sakha and Khakas feature films, which form the core of the studied corpus. Based on interviews of Khakas and Sakha filmmakers, it analyses why and how film can be considered a good vehicle for identity strengthening. Then, focusing on films themselves, be they amateur or more professional quality productions, if not commissioned by the local government, it examines how those films are rethinking the supranational (Russo-Soviet) narrative, re-imagining geography and trying to reconnect with Sakha and Khakas peoples' own past and traditions. Finally, it highlights the differences between Khakas and Sakha cinema through showing how these “national” film productions can express a strong or a weak feeling of identity.